(untitled) (Islamic Sciences Journal, 2024)
ABSTRACT Praise be to God, Lord of the Worlds, and may blessings and peace be upon the Master of all creation, Muhammad (may God’s prayers and peace be upon him), and upon his honorable family and companions. This research was titled “The Quotations of Al-Tahir Ibn Ashour (d. 1393 AH) in his interpretation of Al-Tahrir and Al-Tanweer - Al-Hamdala as an example - This research dealt with collecting and studying the quotes of Imam Ibn Ashour - may God have mercy on him - contained in the interpretation of Al-Hamdala, the second verse of Surat Al-Fatihah, which number (3). Quotations, which are hypothetical or realistic issues raised by Imam Ibn Ashour - may God have mercy on him - in the style of the Qur’an. The aim is to expand the meanings of the Qur’an and extract nice jokes from it. The Qur’an is a word carved from: (If you say: I said) in its various forms. The Imam was creative. Ibn Ashour - may God have mercy on him - in hypothesizing the issues and then answering them. The study included research into the sayings and quotations of previous scholars of Ibn Ashour - may God have mercy on him - in order to clarify whether the previous scholars agreed with his narrations, whether completely or partially, with an explanation of the hypotheses he introduced. I provided a brief explanation of the meaning of each phonogram before delving into its study, and then came up with a result for each phonogram. The nature of the research required that the research consist of an introduction, two sections, then a conclusion, which was presented in the first section: defining the vocabulary of the title, and included three topics: the first: translation of Ibn Ashour, the second: introducing interpretation, and the third: the use of the qanqla among scholars and Ibn Ashour. Then I presented the second topic: Ibn Ashour’s quotes in his interpretation of Al-Hamdala.